Literary study of playing activities to increase the mathematical geometric shapes concept understanding for early childhood students - Riyana, Minuk; Fitrianti, Hariani; Adiatma, Tini; Sari Harahap, Dharma Gyta; Potabuga, Siti Nurjanah; Parkhurst, Helen (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2022)
The background of this study is that learning mathematics in terms of geometry is crucial to introduce to early childhood, and many teachers are still unaware of what activities might boost knowledge of geometric shapes. So, this study aimed to learn about playing activities that can develop an understanding of the concept of mathematical geometric shapes in early childhood. The method employed is a qualitative approach with library research where the data source is secondary data from published research journals. Using labyrinth geometry playing activities, finger painting playing activities, and dakon playing activities, the results for developing knowledge of the notion of geometric shapes in early childhood mathematics may be acquired. The result of this study is based on prior research, namely employing maze geometry playing activities, finger painting playing activities, and dakon playing activities to develop knowledge of mathematical geometry. The point is that playing using geometric shapes provides an understanding of mathematics for early childhood.